CYTOTOXIC EFFECT OF PEPTIDE FUNCTIONALIZED SILVER NANOPARTICLES SYNTHESIZED FROM ALOIN ON BREAST CANCER CELL LINE - ROSE A, LEEMA; S, VIDHYA; PRIYA F, JANEETA; ASHIFA J, SABEENA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the present study is to synthesize the silver (Ag) nanoparticle using Aloin with a focus on its antibacterial, antioxidant, and anticancer activity. Methods: The silver nanoparticles were synthesized using Aloin and were determined by UV-Visible spectrum. It was further characterized by scanning electron microscope (SEM), zeta potential, and dynamic light scattering (DLS). The Fourier transform infrared analysis was also carried out for the Aloin. Results: The UV-Visible absorption spectrum of the synthesized silver nanoparticles has shown the absorption peak at 439nm which proves the formation of silver nanoparticles in the solution. The SEM analysis revealed that the Ag nanoparticles were spherical in shape. The IR spectra showed that there are 6 functional groups are present in Aloin extract. The synthesized nanoparticles are found to be highly stable with an average particle size of 130.7nm which was confirmed by zeta potential and DLS analysis. The synthesized nanoparticles had a good antibacterial and antioxidant activity. It shows a very good cytotoxic effect against breast cancer cell line. Conclusion: The present study suggests that the synthesis route is free from the requirements such as high energy, extended preparation time, and special equipments and thus can be used for large-scale synthesis in food industries for food preservation and these Ag nanoparticles can be used for its therapeutic purposes for developing a new drug against cancer.